Silicon Powder-Based Wafers for Low-Cost Photovoltaics: Laser Treatments and Nanowire Etching - G. Jia; J. Plentz; A. Gawlik; A. S. Azar; G. Stokkan; M. Syvertsen; P. A. Carvalho; J. Dellith; A. Dellith; G. Andrä; A. Ulyashin (International Journal of Photoenergy)
In this study, laser-treated polycrystalline Si (pc-Si) wafers, fabricated by wire sawing of hot-pressed ingots sintered from Si powder, have been investigated. As-cut wafers and those with high-quality thin Si layers deposited on top of them by e-beam have been subjected to laser irradiation to clarify typical trends of structural modifications caused by laser treatments. Moreover, possibility to use laser-treated Si powder-based substrates for fabrication of advanced Si structures has been analysed. It is established that (i) Si powder-based wafers with thicknesses ~180 μm can be fully (from the front to back side) or partly (subsurface region) remelted by a diode laser and grain sizes in laser-treated regions can be increased; (ii) a high-quality top layer can be fabricated by crystallization of an additional a-Si layer deposited by e-beam evaporation on top of the pc-Si; and (iii) silicon nanowires can be formed by metal-assisted wet chemical etching (MAWCE) of polished Si powder-based wafers and as-cut wafers irradiated with medium laser power, while a surface texturing on the as-cut pc-Si wafers occur, and no nanowires can form in the region subject to a liquid phase crystallization (LPC) caused by high-power laser treatments.